(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2023)
The Crawling Framework CAREJOBS (CF) we present here is a suite of tools dedicated to facilitating job search for people with disabilities. In this experimental implementation we propose a crawler with modern architecture based on intelligent agents, a multi-agent system trained on the basis of a rule engine. We also present a case of using CF in a CV creation expert. It can be seen that our approach is perfectible by adding learning to the agent model.